Should Corporations Have the Right to Vote? A Paradox in the Theory of Corporate Moral Agency - Hasnas, John (Journal of business ethics, 2018)
In his 2007 Ethics article, “Responsibility Incorporated,” Philip Pettit argued that corporations qualify as morally responsible agents because they possess autonomy, normative judgment, and the capacity for self-control. Although there is ongoing debate over whether corporations have these capacities, both proponents and opponents of corporate moral agency appear to agree that Pettit correctly identified the requirements for moral agency. In this article, I do not take issue with either the claim that autonomy, normative judgment, and self-control are the requirements for moral agency or the claim that corporations possess them. I claim that if both of these claims are correct, then corporate moral agency entails that, in a liberal democracy, corporations should have the right to vote. I show that under the conception of democracy supported by most liberal political theorists, all parties subject to the law are entitled to the right to vote, and all parties that possess autonomy, normative judgment, and self-control are subject to the law. Therefore, if the proponents of corporate moral agency are correct, then corporations satisfy the requirements for the right to vote. I then consider potential objections to this argument. I show that the strongest objection to the corporate right to vote is undermined by Pettit’s own argument for corporate autonomy. I then show that objections derived from other arguments for limiting the rights of corporations are equally unavailing. I conclude with some observations about the implications of my argument for the question of corporate speech rights.